2014
DOI: 10.1038/onc.2014.315
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 reduces ROS-mediated cell damage via activation of p38

Abstract: Liver kinase B1 (LKB1, also known as serine/threonine kinase 11, STK11) is a tumor suppressor mutated in Peutz-Jeghers syndrome and in a variety of sporadic cancers. Herein, we demonstrate that LKB1 controls the levels of intracellular reactive oxygen species (ROS) and protects the genome from oxidative damage. Cells lacking LKB1 exhibit markedly increased intracellular ROS levels, excessive oxidation of DNA, increased mutation rates, and accumulation of DNA damage, which are effectively prevented by ectopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…Recently, several preclinical studies have suggested a critical role of ROS in cancer therapy [ 8 , 11 15 , 19 , 32 ]. ROS regulation can modulate the cytotoxic effect of taxanes in cancer cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several preclinical studies have suggested a critical role of ROS in cancer therapy [ 8 , 11 15 , 19 , 32 ]. ROS regulation can modulate the cytotoxic effect of taxanes in cancer cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies shed light on the reactive oxygen species (ROS) production induced by anticancer drugs in cancer cells, which may influence the cell death or the drug resistance [ 8 15 ]. ROS are generated by oxidative stress and sometimes associated with the sensitivity or resistance to anticancer drugs [ 8 , 11 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a certain concentration of ROS is bene cial for tissue repair, a large amount of ROS can damage peritoneal mesothelial cells [17,19] . The p38 signaling pathway participates in many physiological processes involved in tissue healing [20] . It has been reported that p38 can promote SOD2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that p38 and its downstream signaling pathway are critical responders to ROS stress, 27,28 and both ROS and p38 regulate apoptosis. 20,29 In the present study, we found that along with ROS increasing, the p38 pathway was activated by A-macB treatment, as evidenced by the increased expression of p-p38 (Thr180/Tyr182) and its downstream target p-HSP27 (Ser82) ( Fig.…”
Section: A-macb Increased Intracellular Ros and Activated The P38 Mapmentioning
confidence: 99%